1994
DOI: 10.1104/pp.106.2.601
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene Production during Development of Mustard (Brassica juncea) and Canola (Brassica napus) Seed

Abstract: An open, continuous flow system was used to investigate ethylene production during degreening of maturing seed of mustard (Brassica juncea cv Cutlass and cv Lethbridge 22A) and canola (Brassica napus cv Westar and cv Alto). lsolated mustard seed evolved higher amounts of ethylene than those of canola, and this was particularly evident both early in embryogeny and later during the desiccation phase of seed maturation. The silique walls produced negligible amounts of ethylene in both species. The concentrations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 7 publications
2
25
0
Order By: Relevance
“…Knowledge on the effects of ethylene on the regulation of different physiological processes that occur during in vitro plant tissue and organ culture, particularly during zygotic and somatic embryogenesis, is still very scant (Matilla and Matilla-Vazquez 2008). During zygotic embryogenesis of Brassica juncea L. and B. napus L., ethylene production peaked at the torpedo stage of embryogenic development (Johnson-Flanagan and Spencer 1994), while in Cicer arietinum, amount of ACC, the activities of ACS and ACO as well as ethylene production reached a maxima at the mid-stage of embryogenesis, declining during late embryogenesis and seed desiccation (Gomez-Jimenez et al 1998). In Brassica rapa L., Rodrigez-Gacio et al (2004) demonstrated that transcript BR ACO1 (one cDNA clone coding for an ACC-oxidase) was accumulated only at the earliest phases of seed embryogenesis and might participate in the highest ACO activity and ethylene production by seeds at the beginning of embryogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge on the effects of ethylene on the regulation of different physiological processes that occur during in vitro plant tissue and organ culture, particularly during zygotic and somatic embryogenesis, is still very scant (Matilla and Matilla-Vazquez 2008). During zygotic embryogenesis of Brassica juncea L. and B. napus L., ethylene production peaked at the torpedo stage of embryogenic development (Johnson-Flanagan and Spencer 1994), while in Cicer arietinum, amount of ACC, the activities of ACS and ACO as well as ethylene production reached a maxima at the mid-stage of embryogenesis, declining during late embryogenesis and seed desiccation (Gomez-Jimenez et al 1998). In Brassica rapa L., Rodrigez-Gacio et al (2004) demonstrated that transcript BR ACO1 (one cDNA clone coding for an ACC-oxidase) was accumulated only at the earliest phases of seed embryogenesis and might participate in the highest ACO activity and ethylene production by seeds at the beginning of embryogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…For shorter-term experiments, embryos (20 DPA) were acclimated by preculture for 3 to 7 d at 21°C under continuous fluorescent light (50 mmol m 22 s 21 ) in petri dishes containing a sterile glass prefilter and 7 mL of culture medium and were then cultured for 3 d in the presence of radiolabel as described below. Since embryos in planta develop under a high (up to 2.5%) CO 2 atmosphere (Johnson-Flanagan and Spencer, 1994;King et al, 1998, we increased the initial content of CO 2 to 2%. The gas headspace was adjusted to contain 2% CO 2 by including a 15-mL glass vial containing 18.6 mg sodium bicarbonate in the culture system.…”
Section: Medium Composition and Embryo Culture Conditionsmentioning
confidence: 99%
“…Although it appears certain that the hormone ethylene participates in the germination process of certain seeds (Kepczynski and Kepzinska 1997;Matilla 2000), its function during zygotic embryogenesis is still far from being fully understood. However, ethylene may be an integral part of normal embryo and seed development in diverse species (Bertrano et al 1994;Ferrá ndiz 2002;Johnson-Flanagan and Spencer 1994;Rodríguez-Gacio et al 2004).…”
Section: Introductionmentioning
confidence: 95%